2019
DOI: 10.1021/acs.est.9b00088
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved Oxygen and Visible Light Irradiation Drive the Structural Alterations and Phytotoxicity Mitigation of Single-Layer Molybdenum Disulfide

Abstract: Understanding environmental fate is a prerequisite for the safe application of nanoparticles. However, the fundamental persistence and environmental transformation of single-layer molybdenum disulfide (SLMoS2, a 2D nanosheet attracting substantial attention in various fields) remain largely unknown. The present work found that the dissolution of SLMoS2 was pH and dissolved oxygen dependent and that alterations in phase composition significantly occur under visible light irradiation. The 1T phase was preferenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 57 publications
(101 reference statements)
1
31
2
Order By: Relevance
“…Rutile TiO 2 nanomaterials (>50 mg/L) induced persistent DNA fragmentation because of free radical generation, while the damage induced by anatase TiO 2 –cell interactions could be repaired . Furthermore, the metallic-phase SLMoS 2 with octahedral coordination (1T-SLMoS 2 ) showed a stronger preference for dissolution in an aqueous environment than semiconductive-phase SLMoS 2 with trigonal prismatic coordination (2H-SLMoS 2 ). , SLMoS 2 can also be degraded by horseradish peroxidase (HRP) . The different properties of NPs lead to their temporary or irreversible adverse effects. , Taken together, the sizes and phase of SLMoS 2 may be crucial for determining the persistence of SLMoS 2 phytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rutile TiO 2 nanomaterials (>50 mg/L) induced persistent DNA fragmentation because of free radical generation, while the damage induced by anatase TiO 2 –cell interactions could be repaired . Furthermore, the metallic-phase SLMoS 2 with octahedral coordination (1T-SLMoS 2 ) showed a stronger preference for dissolution in an aqueous environment than semiconductive-phase SLMoS 2 with trigonal prismatic coordination (2H-SLMoS 2 ). , SLMoS 2 can also be degraded by horseradish peroxidase (HRP) . The different properties of NPs lead to their temporary or irreversible adverse effects. , Taken together, the sizes and phase of SLMoS 2 may be crucial for determining the persistence of SLMoS 2 phytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…17 Furthermore, the metallic-phase SLMoS 2 with octahedral coordination (1T-SLMoS 2 ) showed a stronger preference for dissolution in an aqueous environment than semiconductive-phase SLMoS 2 with trigonal prismatic coordination (2H-SLMoS 2 ). 18,19 SLMoS 2 can also be degraded by horseradish peroxidase (HRP). 20 The different properties of NPs lead to their temporary or irreversible adverse effects.…”
Section: ■ Introductionmentioning
confidence: 99%
“…According to the conduction band potential of MoS 2 nanosheets in reported literature, photo-excited electrons in MoS 2 nanosheets have enough negative potential to directly reduce dissolved oxygens to O 2 •– and H 2 O 2 in the aqueous media. However, • OH cannot be directly produced from the photoinduced holes in MoS 2 nanosheets because their valence band position is not sufficiently positive for oxidizing OH – to • OH. , Therefore, we expect that • OH could be generated by H 2 O 2 decomposition and Mo 6+ reduction under light illumination …”
Section: Resultsmentioning
confidence: 99%
“…As the pH increased, a larger amount of O 2 – was produced. Previous studies revealed that the reaction MoS 2 + 9/2O 2 + 3H 2 O = MoO 4 2– + 2SO 4 2– + 6H + occurred in the aqueous ce-MoS 2 solution. When the pH increased, the reaction would more likely move forward. Thus, the rate of electron transfer from molecular oxygen to form O 2 – under a higher pH could be faster than that under a lower pH .…”
Section: Resultsmentioning
confidence: 99%